Aplikasi Warta Jemaat Gereja GKI FJS Rumainum Menggunakan Kodular: GKI FJS Rumainum Congregational News Application Using Kodular - Meike Agnes Rumere; Julius Panda Putra Naibaho; Cristian Dwi Suhendra (JISTECH: Journal of Information Science and Technology, 2023)
GKI FJS Rumainum Church is a split church from GKI Utrecht Sauabas, which was founded on June 13 until now. However, the church announcement system that uses paper is still ineffective and inefficient. Therefore, this research aims to develop an Android application that minimizes errors, facilitates the delivery of information, and saves the cost of making church newsletters. Data collection methods include observation, interviews, and literature study. Application development uses the waterfall method, through the stages of analysis, design, implementation with Kodular, and testing. The result is the FJS Rumainum Church Congregational Warta application which was successfully created using Kodular and MySQL tools. This application has a menu about the church, worship schedule, information, and login. Application testing uses the BlackBox method and the results of the tests show good results, meet the specifications set and are expected to help church members get accurate information.